2014
DOI: 10.1002/ps.3830
|View full text |Cite
|
Sign up to set email alerts
|

Female detection of the synthetic sex pheromone contributes to the efficacy of mating disruption of the European grapevine moth, Lobesia botrana

Abstract: In addition to reducing the ability of males to locate females, the mating-disruption technique can suppress pest numbers as a consequence of its direct effects on females. The two mechanisms probably act synergistically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
1
17
0
1
Order By: Relevance
“…Moreover, by the time a male locates a female colony, the females have aged and their fecundity has deteriorated (Fitzpatrick, ; Ross et al., ). In fact, it was suggested that moth (Harari et al., ) and P. ficus (Walton et al., ) fertile females deposit fewer eggs in MD plots. Finally, Jones & Aihara‐Sasaki () have proposed a synergetic effect between decreased oviposition and delayed mating, as older females may die before laying their full egg complement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by the time a male locates a female colony, the females have aged and their fecundity has deteriorated (Fitzpatrick, ; Ross et al., ). In fact, it was suggested that moth (Harari et al., ) and P. ficus (Walton et al., ) fertile females deposit fewer eggs in MD plots. Finally, Jones & Aihara‐Sasaki () have proposed a synergetic effect between decreased oviposition and delayed mating, as older females may die before laying their full egg complement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a great deal more research needs to be carried out, examining a range of species with a variety of biological traits (e.g., monandrous and polyandrous, host-plant specialists and generalists, migrants and non-migrants) to determine whether any general rules exist. It is also important from an applied perspectiveautodetection may be an overlooked factor affecting the efficacy of mating disruption programs (Stelinski et al, 2006;Harari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous research in apple orchards (Li et al ., ). Mating disruption is an environmentally safe pest control method that has allowed growers to reduce insecticide use significantly (Harari et al ., ). However, the main problem was maintaining the lures effectively and reducing the cost of lures and distribution (Gaston et al ., ).…”
Section: Discussionmentioning
confidence: 97%